واقع و طبيعة مناخ الاستثمار في الجزائر و انعكاسو على الدور التنموي للقطاع الخاص في دعم التنمية - الاقتصادية، دراسة تحليلية لمؤشرات أداء الأعمال للفترة 0202 2: The reality and nature of the investment climate in Algeria and its reflection on the role of the private sector in supporting economic development, analytical study of business performance indicators during the period 2010-2020 - بوكفوسة محجوبة,; شوام بوشامة, (Journal of North African Economies, 2025)
This research paper aims to study the reality and nature of the investment climate in Algeria and its reflection on activating the developmental role of the private sector by analyzing and evaluating business performance indicators during the period 2010-2020, as the contemporary world witnessed many developments and changes that affected all economic, political and social fields. Especially with the increase in various economic crises and the emergence of signs of a new world order that aims to open markets, liberalize trade, Encouraging competition and pushing the private sector towards contributing to economic development, as we found in our study that despite the efforts made by Algeria to improve its investment environment to attract the largest number of investment projects and provide them with many incentives and facilities, it is still suffering from several Problems and obstacles that prevent the private sector from playing an effective role in economic development.